1999
DOI: 10.1159/000027643
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals in the Guinea Pig Inner Ear following Gentamicin Exposure

Abstract: The purpose of this study was to investigate the occurrence of free radicals, nitric oxide (NO), superoxide (O2) and peroxynitrite, in the inner ear of the guinea pig following intratympanic injection with 5 mg of gentamicin (GM). Forty-eight hours after GM injection, varying degrees of degeneration of the inner ear were observed. Immunohistochemical study revealed immunoreactivity to NO synthase II (which generates NO) and to xanthine oxidase (which generates O2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 33 publications
3
63
0
1
Order By: Relevance
“…ROS scavengers and glutamate antagonists have been shown to provide protection from cochlear and vestibular damage by aminoglycoside, cisplatin or noise [1,6,7,9,16]. Furthermore, such damage is prevented by NOS inhibitors or scavengers of peroxynitrite [3,[8][9][10]. As already reported, L-NAME inhibits the production of NO [9,13], while D-met reduced the production of ROS [7].…”
Section: Discussionmentioning
confidence: 99%
“…ROS scavengers and glutamate antagonists have been shown to provide protection from cochlear and vestibular damage by aminoglycoside, cisplatin or noise [1,6,7,9,16]. Furthermore, such damage is prevented by NOS inhibitors or scavengers of peroxynitrite [3,[8][9][10]. As already reported, L-NAME inhibits the production of NO [9,13], while D-met reduced the production of ROS [7].…”
Section: Discussionmentioning
confidence: 99%
“…In gentamicin cytotoxicity, depletion of intracellular GSH levels may be associated with an increase in reactive oxygen species. Many authors have suggested the participation of free oxygen radicals and nitric oxide in the adverse renal and cochlear effects of aminoglycosides [Lopez-Gonzalez et al, 1998Priuska and Schacht, 1995;Schacht, 1998, 1999b;Takumida et al, 1999]. The involvement of free radicals has been proven by the attenuation of gentamicin cytotoxicity and ototoxicity by antioxidants and iron chelators [Lopez-Gonzalez et al, 2000;Schacht, 1999c, 2000;Song et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that free radical generation plays a central role in this toxicity [Priuska and Schacht, 1995;Baliga et al, 1997;Lopez-Gonzalez et al, 1999;Sha and Schacht, 1999a, b;Walker et al, 1999]. In particular, hair cell death occurs by apoptosis [Takumida et al, 1999;Forge, 1985;Nakagawa et al, 1998], probably induced by a mechanism involving free radical formation and lipid peroxidation [Forge and Schacht, 2000]. Accordingly, in vivo and in vitro experiments confirmed that several radical scavengers [Garetz et al, 1994a, b] and iron chelators attenuate aminoglycoside-induced ototoxicity and nephrotoxicity [Conlon et al, 1998[Conlon et al, , 1999Sha and Schacht, 2000;Song and Schacht, 1996;Song et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Within the avian and rodent cochlea, elevated ROS levels have been detected within hair cells following aminoglycoside exposure (6)(7)(8)(9)(10)(11). Augmentation with various antioxidants in vitro and in vivo has proven to be partially effective at ameliorating aminoglycoside ototoxicity (12)(13)(14)(15)(16)(17)(18), suggesting a causal link between ROS production and hair cell death. However, antioxidants generally do not protect across a wide range of antibiotic doses and do not distinguish between the origins of ROS, leaving the source of ROS production during aminoglycoside-induced hair cell death an open question.…”
Section: Introductionmentioning
confidence: 99%